A Tool for Brain-Wide Quantitative Analysis of Molecular Data upon Projection into a Planar View of Choice - Vreysen, Samme; Scheyltjens, Isabelle; Laramée, Marie-Eve; Arckens, Lutgarde (Frontiers in Neuroanatomy, 2017)
Several techniques, allowing the reconstruction and visualization of functional, anatomical or molecular information from tissue and organ slices, have been developed over the years. Yet none allow direct comparison without reprocessing the same slices. Alternative methods using publicly available reference maps like the Allen Brain Atlas lack flexibility with respect to age and species. We propose a new approach to reconstruct a segmented region of interest from serial slices by projecting the optical density values representing a given molecular signal to a plane of view of choice, and to generalize the results into a reference map, which is built from the individual maps of all animals under study. Furthermore, to allow quantitative comparison between experimental conditions, a non-parametric pseudo t-test has been implemented. This new mapping tool was applied, optimized and validated making use of an in situ hybridization dataset that represents the spatiotemporal expression changes for the neuronal activity reporter gene zif268, in relation to cortical plasticity induced by monocular enucleation, covering the entire mouse visual cortex. The created top view maps of the mouse brain allow precisely delineating and interpreting eleven extrastriate areas surrounding mouse V1. As such, and because of the opportunity to create a planar projection of choice, these molecular maps can in the future easily be compared with functional or physiological imaging maps created with other techniques such as Ca2+, flavoprotein and optical imaging.